2023
DOI: 10.1002/fsn3.3431
|View full text |Cite
|
Sign up to set email alerts
|

Impact of various extraction methods on fatty acid profile, physicochemical properties, and nutritional quality index of Pangus fish oil

Abstract: Marine fish are high in essential omega‐3 fatty acids, which are important for human health. This study evaluated the effects of four extraction methods (soxhlet extraction, SE; wet rendering, WR; acid silage, AS; microwave‐assisted extraction, MAE) on the oil yield, physicochemical properties, fatty acid profile, and nutritional quality index (NQI) of pangus fish oil. The oil yield ranged from 13.50% to 21.80%, with MAE having the highest yield. Furthermore, MAE oil has the lowest free fatty acid (0.70%), per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This concordance underscores the ethanol-assisted enzymatic hydrolysis method's strong reproducibility and operational feasibility. Nahidur Rahman et al [37] discussed the effect of different extraction methods of pangus fish oil on the extraction rate and found that the microwave-assisted extraction method, the aqueous extraction, and the acidic silage method did not provide more than a 30% extraction rate. Ella Aitta et al [7] used alcalase, neutrase, and protamex to extract fish oil from sea herring with extraction rates ranging from 37 to 58%.…”
Section: Response Surface Optimization Experiments For Extracting Dot...mentioning
confidence: 99%
“…This concordance underscores the ethanol-assisted enzymatic hydrolysis method's strong reproducibility and operational feasibility. Nahidur Rahman et al [37] discussed the effect of different extraction methods of pangus fish oil on the extraction rate and found that the microwave-assisted extraction method, the aqueous extraction, and the acidic silage method did not provide more than a 30% extraction rate. Ella Aitta et al [7] used alcalase, neutrase, and protamex to extract fish oil from sea herring with extraction rates ranging from 37 to 58%.…”
Section: Response Surface Optimization Experiments For Extracting Dot...mentioning
confidence: 99%
“…Moreover, broiler chickens fed with BSFL oil exhibited improved immune and antioxidant functions in the blood plasma [15]. Fatty acid profiles, extraction yields, and antioxidant properties of oils can vary depending on the extraction method employed [16].…”
Section: Introductionmentioning
confidence: 99%